If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -3w = 5(-1w + -5) + -3(2w + -3) Reorder the terms: 6 + -3w = 5(-5 + -1w) + -3(2w + -3) 6 + -3w = (-5 * 5 + -1w * 5) + -3(2w + -3) 6 + -3w = (-25 + -5w) + -3(2w + -3) Reorder the terms: 6 + -3w = -25 + -5w + -3(-3 + 2w) 6 + -3w = -25 + -5w + (-3 * -3 + 2w * -3) 6 + -3w = -25 + -5w + (9 + -6w) Reorder the terms: 6 + -3w = -25 + 9 + -5w + -6w Combine like terms: -25 + 9 = -16 6 + -3w = -16 + -5w + -6w Combine like terms: -5w + -6w = -11w 6 + -3w = -16 + -11w Solving 6 + -3w = -16 + -11w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '11w' to each side of the equation. 6 + -3w + 11w = -16 + -11w + 11w Combine like terms: -3w + 11w = 8w 6 + 8w = -16 + -11w + 11w Combine like terms: -11w + 11w = 0 6 + 8w = -16 + 0 6 + 8w = -16 Add '-6' to each side of the equation. 6 + -6 + 8w = -16 + -6 Combine like terms: 6 + -6 = 0 0 + 8w = -16 + -6 8w = -16 + -6 Combine like terms: -16 + -6 = -22 8w = -22 Divide each side by '8'. w = -2.75 Simplifying w = -2.75
| 6y+2=-2y+26 | | 4v-10=54 | | y/6-3=4 | | -6n+16-3n+9=n-40 | | r/14=13 | | 5m-4=2m+23 | | 5/7x=105 | | r^2+8r-0=20 | | d+118=907 | | 85x-4-9x=18+76x-22 | | 5/9(86-32) | | -4x+8x-5=4(x-1)-17 | | 71.43x=105 | | 3k+9=30 | | 4(y-5)+2=5 | | 3(3x+9)=9-2(x-9) | | 21p=819 | | s=bd-9 | | r/11=20 | | 3/8-5/15 | | 2c+8=-10c | | y=2x+45 | | 23-5x=32 | | 6-9x=7x+8 | | 3(5+x)=3 | | 88-1/3x9 | | 24=s/-22 | | 4-x-3x=-8 | | 3/4w-12w-4=12 | | 2x-4(3-2x)=4(x-5)-28 | | 150w+2=195w+1 | | 432=27v |